2021
DOI: 10.3390/biology10121327
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Accuracy and Function of Different Thermometry Techniques for Measuring Body Temperature

Abstract: The purpose of this study was to determine which thermometry technique is the most accurate for regular measurement of body temperature. We compared seven different commercially available thermometers with a gold standard medical-grade thermometer (Welch-Allyn): four digital infrared thermometers (Wellworks, Braun, Withings, MOBI), one digital sublingual thermometer (Braun), one zero heat flux thermometer (3M), and one infrared thermal imaging camera (FLIR One). Thirty young healthy adults participated in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…5 Due to its noninvasive, convenient, hygienic, and quick nature, the infrared ear thermometer has been widely applied in clinical practice. [6][7][8] However, it is rarely used for intraoperative temperature monitoring, as its accuracy remains controversial. [11][12][13] Recently, Mah et al 7 compared seven different commercially available thermometers and found that the infrared ear thermometer was the most accurate device for the regular measurement of body temperature; conversely, Mogensen et al 14 found that although the infrared ear thermometer was able to detect fever (defined as ≥38°C rectally) using a cut point of 37.5°C, it was not accurate enough to measure the exact temperature in an adult emergency department population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Due to its noninvasive, convenient, hygienic, and quick nature, the infrared ear thermometer has been widely applied in clinical practice. [6][7][8] However, it is rarely used for intraoperative temperature monitoring, as its accuracy remains controversial. [11][12][13] Recently, Mah et al 7 compared seven different commercially available thermometers and found that the infrared ear thermometer was the most accurate device for the regular measurement of body temperature; conversely, Mogensen et al 14 found that although the infrared ear thermometer was able to detect fever (defined as ≥38°C rectally) using a cut point of 37.5°C, it was not accurate enough to measure the exact temperature in an adult emergency department population.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that a difference of <0.2°C between measurements of the two temperatures would be clinically insignificant, 7 with a sample size of 26 achieves 90% power to detect a mean of paired differences of 0.2°C with an estimated standard deviation (SD) of 0.3°C and with a significance level (α) of 0.05, using a two-sided paired t test. We recruited 50 patients to compensate for possible losses and protocol violations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different types of body temperature scanners in the market such as digital thermometer, digital ear thermometer, forehead thermometer, thermal camera, mercury thermometer etc. (Mah et al 2021). Thermal imaging camera (TIC) is one of the applications based on the proven technology -infrared thermography, it provides effective real-life temperature monitoring of an objects in contactless way (Bagavathiappan et al 2013).…”
Section: Thermal Imaging Camera (Tic)mentioning
confidence: 99%
“…Although temperature screening is not an effective way to avert an epidemic due to its low specificity, it can likely be used as part of a primary screening because of its increased sensitivity. This could be due to inadequate instrumentation and calibration methods and a lack of acceptable, regularly executed standardised deployment and screening procedures [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%